Handbook of clinical issues in couple therapy - Wetchler, Joseph L. (Routledge, 2011)
Handbook of Clinical Issues in Couple Therapy is a comprehensive overview of emerging issues that impact couple therapy, all in a single volume. While other guides concentrate more on the approaches themselves, this invaluable source provides the latest research and perspectives every clinician needs when dealing with challenging issues often found in practice. Practitioners get a clear view of the aspects of problems they must consider to be most effective when providing therapy to couples. The text is fully referenced.